BENTUK TINDAK TUTUR REPRESENTATIF PADA PERCAKAPAN GRUP WHATSAPP KARANG TARUNA SALAMA NGLESES, PANDEYAN, SUKOHARJO - Wiwit Nur Fatyimah; Farida Nugrahani (Bahtera Indonesia, 2023)
This study aims to determine the forms of reprensentative speech acts in conversations via WhatsApp at the Karang Taruna Salama Ngleses Group, Pandeyan, Sukoharjo. The method used in this study is a qualitative descriptive method. The data collection techniques used are documentation techniques and data faliditation recording techniques are pursued through triangulation. The data analysis used in this study is pragmatic by carrying out an interactive model. The results showed that there are 4 forms of representative speech acts in the Whatapp karan taruna group, namely speech (1) stating, (2) reporting, (3) showing, (4) proposing.